Freedom fighter - Destiny Image Films; Copyright Collection (Library of Congress) (2012)
"Follows the efforts of Rev. Majed and his organization One Free World International over a four year period, as he travels to Pakistan and Afghanistan to investigate claims of abuse, persecution and slavery."--Case insert.
Title from container.
Sources used: videodisc container; Copyright catalog online; Amazon WWW site, viewed June 8, 2020; Internet movie database WWW site, viewed June 8, 2020; PR newswire WWW site, viewed June 8, 2020.
Winner - Gold Award - California Film Awards; Winner - Best International Documentary - San Diego Christian Film Festival; Winner - Best Documentary Feature - Colorado Film Awards
Keywords: Persecution; Documentary films; Feature films; Nonfiction films